2017
DOI: 10.1007/s11695-017-2872-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy Versus Banded Roux-en-Y Gastric Bypass for Diabetes and Obesity: a Prospective Randomised Double-Blind Trial

Abstract: Prospectively registered at Australia and New Zealand Clinical Trials Register (ACTRN 12611000751976) and retrospectively registered at Clinical Trials (NCT1486680).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…The literature search identified 2650 unique citations, whereof 2625 were excluded because of irrelevant content, duplication, or non‐English language (Figure ). Of the 25 studies that were full‐text screened, 13 did not meet the inclusion criteria either because follow‐up time was too short, the authors did not differentiate between improvement and remission of T2DM, other bariatric procedures were performed (mini gastric bypass, banded RYGB, and metabolic gastric bypass), the study was not an RCT, no patients in the SG‐group had T2DM, or the study included a subpopulation of an already included RCT . We detected two studies that had been performed in the same study population, and of these, only the study referring to a clinical trial registry number was included .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 2650 unique citations, whereof 2625 were excluded because of irrelevant content, duplication, or non‐English language (Figure ). Of the 25 studies that were full‐text screened, 13 did not meet the inclusion criteria either because follow‐up time was too short, the authors did not differentiate between improvement and remission of T2DM, other bariatric procedures were performed (mini gastric bypass, banded RYGB, and metabolic gastric bypass), the study was not an RCT, no patients in the SG‐group had T2DM, or the study included a subpopulation of an already included RCT . We detected two studies that had been performed in the same study population, and of these, only the study referring to a clinical trial registry number was included .…”
Section: Resultsmentioning
confidence: 99%
“…However, in this review, the landmark STAMPEDE trial and the RCT by Keidar et al were not included in the meta‐analysis of studies with 1‐year follow‐up . This review also differed from the present review considering that other variants of gastric bypass, such as banded and mini gastric bypass, were included, and understandably, it could not include the recently published results from the Oseberg‐trial.…”
Section: Discussionmentioning
confidence: 95%
“…In the context of T2D remission, only one study has focused on the comparison of microbial changes between patients experiencing or not experiencing DR post-BS 148 . Even though only 14 patients were examined (7 RYGB, 7 VSG), Murphy et al, showed that presurgical GM composition differed between patients who eventually experienced DR as compared to those who did not.…”
Section: Gut Microbiota Compositional Modificationsmentioning
confidence: 99%
“…The two most widely used types of bariatric surgery are currently VSG and Roux-n-Y-Gastric-Bypass (46). Despite the similar metabolic outcomes between the two procedures, VSG is reported to have lower mortality in mice (47,48), but also allows for gradual weight regain, which is why it was chosen for this study (11,49).…”
Section: Discussionmentioning
confidence: 99%